Laboratory characterization of residual sludge from natural gas extraction by hydraulic fracturing in the Burgos Basin, Mexico. Issue 3 (2nd October 2018) - Maldonado-Torres, Aracely; Mora Ravelo, Sandra Grisell; Osorio Hernández, Eduardo; Olvera Velona, Angeluz; López Santillán, José Alberto; Estrada-Drouaillet, Benigno
Abstract: Pollutants and microbiota present in the residual sludge of hydraulic fracturing were determined and characterized physicochemically. Analyses included determination of pH, electric conductivity, organic matter percentage, as well as total carbonates, inorganic nitrogen and extractable phosphorous. In addition, presence of hydrocarbons by gas chromatography, potentially toxic elements (PTEs) by atomic absorption and presence of radioactive isotopes by gamma spectrometry were determined. Moreover, fungi and bacteria present in the residual sludge were classified taxonomically to the level of genus. Medium and heavy hydrocarbon fractions were found in concentrations above the maximum limits permitted (MLP) by Mexican environmental norms. Cu, Pb, Zn, Fe and Mg, however, were below the MLP. Likewise, gamma spectrometry analysis revealed naturally occurring Ac 228, Ra 226 and K 40 . The microbiological analysis found presence of the bacteria Bacillus spp., Micrococcus sp., Diplococcus sp. and Staphylococcus sp. and the fungi Trichoderma sp., Aspergillus sp. and Penicillium spp.